Crimean-Congo haemorrhagic fever virus in ticks, domestic, and wild animals - Celina, Seyma S.; Italiya, Jignesh; Tekkara, Allan Obonyom; Černý, Jiří (Frontiers in Veterinary Science, 2025)
Crimean-Congo haemorrhagic fever virus (CCHFV) poses a significant public health threat due to its potential for causing severe disease in humans and its wide geographic distribution. The virus, primarily transmitted by Hyalomma ticks, is prevalent across Africa, Asia, Europe, and the Middle East. Understanding the virus’s spread among tick populations is crucial for assessing its transmission dynamics. Vertebrates play a key role in CCHF epidemiology by supporting tick populations and acting as virus carriers during viremia. Livestock, such as cattle, sheep, and goats, amplify the virus and increase tick numbers, posing zoonotic risks. Wildlife, while asymptomatic, can serve as reservoirs. Birds generally do not show signs of the virus but can introduce infected ticks to new regions. This review compiles information on CCHFV’s tick vectors and vertebrate hosts, emphasizing their roles in the virus’s transmission dynamics. Understanding these dynamics is essential for developing effective control and prevention strategies.